KnockoutJS by example : develop rich, interactive, and real-world web applications using knockout.js - Jaswal, Adnan (Community experience distilled., 2015)
Develop rich, interactive, and real-world web applications using knockout.js About This Book Master the full range of features provided by knockout.js such as declarative binding, automatic refresh, dependency tracking, and templating using this project based guide Tackle real-world problems such as page navigation, forms, composite UI components, maps integration, server interaction for CRUD operations, and application security Discover the power of knockout.js as you build applications with complexity ranging from beginner to advanced Extend and customize knockout.js to harness its full potential Integrate with third party libraries and APIs to build fully featured applications In Detail KnockoutJS By Example is a project-based guide that introduces the key features and concepts of knockout.js. It helps you create an application skeleton and a Hello World application. You will develop a To-Do list application that aims to show the basic features of knockout.js in action, such as data binding and observables, following which you will develop a dynamic online customer registration form that captures and validates customer information. This book will further walk you through developing a customer banking portal, which demonstrates the use of knockout.js with components such as navigation bars, tabs, carousels, master details view, panels, forms, and wizards. You will also discover how to use token-based authentication and authorization to secure the customer banking portal, and move on to creating an editable products grid with CRUD operations. Finally, you will explore how to use the Google Maps API with knockout.js. KnockoutJS By Example will not only leave you with a basic understanding of knockout.js fundamentals but also take you through some of the advanced features. It will help you get a web application up and ready instantly. What You Will Learn Explore the basic concept behind the Model-View-View Model (MVVM) design pattern and how it is implemented by knockout.js Develop a modular application skeleton based on the Module Pattern that can be used as a template for your projects Use knockout.js with other libraries and APIs, such as JQuery, Bootstrap, and the Google Maps API, to give your users a richer experience Create real-world dynamic web forms to capture user information and learn how knockout.js makes it easier to capture, validate, and submit form data Develop and use dynamic UI components such as grids, tabs, master details view, and wizards Extend knockout.js to add custom extenders, binding handlers, subscribers, and observables Secure your single page application using token-based authentication Who This Book Is For This book is intended for designers and developers who want to learn how to use Knockout to develop rich, interactive, and modular web applications. The book assumes no prior knowledge of the Knockout library but basic familiarity with HTML, CSS, and JavaScript would be helpful. Style and approach The book takes an iterative approach in explaining and building the sample applications. The applications are built in small portions with each portion delivering a set of features. It is an easy-to-follow yet comprehensive hands-on guide, which is full of real-world applications. Downloading the example code for this book You can download the example code files for all Packt books you have purchased from your account at http://www.PacktPub.com. If you purchased this book elsewhere, you can visit http://www.PacktPub.com/support and register to have the files e-mailed directly to you.